Understanding Molecular Mechanisms of the Brain Through Transcriptomics - Wang, Wei; Wang, Guang-Zhong (Frontiers in Physiology, 2019)
The brain is the most complicated organ in human body. Its complexity is not only reflected that it is composed of various brain regions, but also because of these brain regions have different functions. The complexity of each brain region lies in the fact that each region has different gene expression profiles, the possibility of differential RNA splicing, as well as various post-transcriptional and translational modification processes. Understanding the complexity of the brain at the molecular level is important for a comprehensive understanding of how the brain works. Fortunately, the development of next generation sequencing technology has made it possible to measure the molecular activity of a specific tissue as a daily routine approach of research. Therefore, at the molecular level, the application of sequencing technology to investigate the principle of the brain has become a novel field, and many important findings have been discovered in this field. In this paper, we reviewed the major methods used in the analysis of brain transcriptome, including the application of these methods in the research of human and non-human mammal brains. Finally, we discussed the utilization of transcriptome methods in neurological diseases. It is worth noting that this field is rapidly moving forward, especially the recent rise of single-cell transcriptome technology, which deserves our future attention.